Liquid crystal display light guide plate TPE protective film and preparation method thereof

By adding modified nano calcium carbonate and modified SBS to the protective film material of the liquid crystal display light guide plate, the problems of insufficient aging of the existing protective film, residual glue and antibacterial effects are solved, and high tensile strength, aging resistance and excellent antibacterial flame retardant effects are achieved.

CN119859372APending Publication Date: 2025-04-22SHAOXING JUCHENG NEW MATERIAL TECH CO LTD +1

Patent Information

Application Number
CN202510116124.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The protective film of the existing liquid crystal display light guide plate is prone to aging during use, the residual glue and antibacterial effects are insufficient, and the flame retardant performance is limited, which limits its use range.

Method used

By adding modified nano calcium carbonate and modified SBS to the protective film material, combined with lubricant and plasticizer, a liquid crystal display light guide plate TPE protective film with excellent tensile strength, aging resistance and antibacterial flame retardant effect was prepared.

Benefits of technology

It achieves good tensile strength of the protective film, heat-resistant oxygen aging performance and significant antibacterial and flame retardant effects, extends the service life of the light guide plate and improves user health and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005257859570000021
    Figure BDA0005257859570000021
  • Figure BDA0005257859570000111
    Figure BDA0005257859570000111
  • Figure FDA0005257859560000011
    Figure FDA0005257859560000011
Patent Text Reader

Abstract

The invention relates to the field of protective films, and discloses a liquid crystal display light guide plate TPE protective film and a preparation method thereof, the protective film comprises modified SBS, polypropylene, modified nano calcium carbonate, a lubricant and a plasticizer; the modified nano calcium carbonate is prepared by grafting a modified additive on the surface of nano calcium carbonate through chemical reaction and then coordinating with copper ions; the modified additive is prepared by preparing a chlorinated silicon-containing intermediate by using dichlorodiphenyl silane, diethylene glycol and cyanuric chloride as raw materials and then grafting a component I and 3-aminopropyltrimethoxysilane; the component I is prepared from 5-chloromethylthiazole and p-phenylenediamine through a reaction, and the modified SBS is prepared from epoxidized SBS and nano titanium dioxide subjected to amination modification by 3-aminopropyltriethoxysilane through a ring-opening reaction. The film material is endowed with excellent tensile strength, aging resistance and antibacterial and flame-retardant effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of protective films, and in particular relates to a TPE protective film for a liquid crystal display light guide plate and a preparation method thereof. Background Art

[0002] The light guide plate used in the LCD screen of mobile phones, cameras and other digital electronic products is a highly transparent and high-purity product, which has very high requirements for the production environment and surface quality. However, during the processing, handling and transportation of the light guide plate, it is inevitable that it will come into contact with certain parts of the equipment, or due to improper operation, it will cause scratches or adhesion of dust and oil, so a protective film needs to be attached to the surface of the light guide plate.

[0003] Thermoplastic elastomer is a multifunctional polymer material that not only has the processability of thermoplastics, but also has the elasticity of vulcanized rubber. It can be mass-processed and produced through processes such as melt extrusion or injection molding, and is widely used in electrical appliances, automobiles, medical equipment, construction, and sporting goods. At present, after the protective film applied to the light guide plate is attached to the surface of the light guide plate, the protective film will age over time due to the influence of temperature and ultraviolet rays, resulting in residual glue after the protective film cannot be peeled off smoothly after use, affecting the quality of the light guide plate. In addition, the existing LCD screen is easily contaminated with a large amount of dust and bacteria. Antibacterial LCD screen protective film can effectively inhibit bacterial growth and protect the health of users, but conventional thermoplastic elastomer protective films have limited flame retardancy and insufficient antibacterial effect, which to a certain extent limits its scope of use.

[0004] In addition, a Chinese patent with application number CN202110446591.5 discloses a uniform, stable, wear-resistant TPE material and a preparation method thereof. An antioxidant is added to the raw material composition. The use of this additive to modify the TPE material can effectively improve the high-temperature aging resistance of the TPE material. However, conventional small molecule antioxidants are easy to volatilize and migrate during the processing and subsequent use of TPE materials, thereby contaminating the surface of the light guide plate, and the long-term antioxidant performance of the TPE material cannot be guaranteed. Summary of the invention

[0005] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a TPE protective film for a liquid crystal display light guide plate and a preparation method thereof, and by adding modified nano-calcium carbonate and modified SBS, the film material is endowed with excellent tensile strength, aging resistance and antibacterial and flame retardant effects.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A liquid crystal display light guide plate TPE protective film comprises the following components in parts by weight: 60-80 parts of modified SBS, 10-20 parts of polypropylene, 5-10 parts of modified nano calcium carbonate, 1-3 parts of lubricant, and 0.5-1.5 parts of plasticizer;

[0008] The modified nano-calcium carbonate is prepared by grafting a modified additive on the surface of the nano-calcium carbonate by chemical reaction and then coordinating with copper ions; wherein the modified additive is prepared by using diphenyldichlorosilane, diethylene glycol, and cyanuric chloride as raw materials to prepare a chlorinated silicon-containing intermediate, and then grafting component one and 3-aminopropyltrimethoxysilane; wherein component one is prepared by a substitution reaction between 5-chloromethylthiazole and p-phenylenediamine;

[0009] The structural formula of the chlorinated silicon-containing intermediate is as follows:

[0010]

[0011] The modified SBS is prepared by a ring-opening reaction between epoxidized SBS and nano-titanium dioxide modified by amination with 3-aminopropyltriethoxysilane.

[0012] Preferably, the lubricant is one or more of stearic acid, polyethylene wax, oxidized polyethylene wax, and paraffin; the plasticizer is one or more of dibutyl phthalate, diisononyl phthalate, tributyl citrate, and acetyl tributyl citrate.

[0013] Preferably, the preparation method of the modified nano calcium carbonate comprises the following steps:

[0014] (1) diphenyldichlorosilane and diethylene glycol are placed in a reactor, tetrahydrofuran solvent is added, and the reaction is stirred for 5 to 7 hours. During the reaction, triethylamine is added in batches to remove hydrogen chloride generated by the reaction. After the reaction is completed, the reaction is filtered, rotary evaporated, and dried to prepare a silicon-containing intermediate;

[0015] (2) Put the silicon-containing intermediate and sodium hydroxide in a reactor, add tetrahydrofuran solvent, heat to 80-95° C., reflux for 1-2 hours, cool to room temperature after the reaction is completed to obtain a mixed solution, put cyanuric chloride and acetone in a reactor, slowly dropwise add the mixed solution and continue to react for 3-5 hours, filter and dry after the reaction is completed to prepare a chlorinated silicon-containing intermediate;

[0016] (3) 5-chloromethylthiazole and triethylamine are placed in a reactor, acetonitrile solvent is added, the temperature is raised to 45-55° C., p-phenylenediamine is added, and stirred for 2-5 hours. After the reaction is completed, the mixture is subjected to rotary evaporation, filtration, and drying to prepare component 1;

[0017] (4) taking the chlorinated silicon-containing intermediate and triethylamine into a reactor, adding acetonitrile solvent, heating to 40-60° C., adding component 1 and stirring the reaction for 4-7 hours, then adding a mixed solution of 3-aminopropyltrimethoxysilane and acetonitrile, continuing to stir the reaction for 4-6 hours, and after the reaction is completed, rotary evaporation, washing, and drying are performed to prepare a modified additive;

[0018] (5) dispersing nano-calcium carbonate in toluene by ultrasonic method to obtain a suspension, dissolving the modified additive in toluene to obtain a mixed solution, adding the mixed solution to the suspension, stirring and reacting at 85-95° C. for 5-7 hours, and filtering, washing and drying after the reaction is completed to obtain functionalized nano-calcium carbonate;

[0019] (6) The functionalized nano-calcium carbonate is ultrasonically dispersed in anhydrous ethanol to obtain a dispersion, and then a mixed solution of copper acetate and anhydrous ethanol is added, and the mixture is stirred and reacted at 60-75° C. for 2-3 hours. After the reaction is completed, the modified nano-calcium carbonate is prepared by filtration, washing, and drying.

[0020] Preferably, in step (1), the molar ratio of diphenyldichlorosilane to diethylene glycol is 1:2.2-2.7.

[0021] Preferably, in step (2), the molar ratio of the silicon-containing intermediate, sodium hydroxide and cyanuric chloride is 1:2-2.1:2-2.2.

[0022] Preferably, in step (3), the molar ratio of 5-chloromethylthiazole to p-phenylenediamine is 1:1 to 1.3.

[0023] Preferably, in step (4), the molar ratio of the chlorinated silicon-containing intermediate, component one and 3-aminopropyltrimethoxysilane is 1:2-2.2; 2-2.2.

[0024] Preferably, in step (5), the mass ratio of nano-calcium carbonate to the modified additive is 1:0.5-2.

[0025] Preferably, the preparation method of the modified SBS comprises the following steps:

[0026] A. Take SBS in a reactor, add cyclohexane solvent, heat and stir until SBS is dissolved, then add formic acid, PEG-400 and hydrogen peroxide, stir and react at 65-80°C for 2-3h, cool to room temperature after the reaction is completed, precipitate with anhydrous ethanol, wash and dry to prepare ESBS;

[0027] B. Ultrasonic dispersion of nano-titanium dioxide in anhydrous ethanol, then adding 3-aminopropyltriethoxysilane, stirring and reacting at 75-90° C. for 6-8 hours, cooling to room temperature after the reaction is completed, filtering, washing and drying to prepare amino-modified nano-titanium dioxide;

[0028] C. Take ESBS in a reactor, add cyclohexane solvent, heat to 65-75°C, stir to dissolve, add sodium hydroxide solution and amino-modified nano-titanium dioxide, stir to react for 2.5-4h, cool to room temperature after the reaction is completed, precipitate with anhydrous ethanol, wash and dry to prepare modified SBS.

[0029] The method for preparing the TPE protective film for a liquid crystal display light guide plate as described above comprises the following steps:

[0030] S1, adding parts by weight of modified SBS, polypropylene, modified nano calcium carbonate, lubricant and plasticizer into a mixer, mixing at 40-60° C. for 5-10 min to obtain a premix;

[0031] S2, extruding and granulating the premixed material at 170-200° C. in a twin-screw extruder to obtain a mixed material;

[0032] S3, blow molding the mixed material to prepare a TPE protective film for a liquid crystal display light guide plate.

[0033] Beneficial effects of the present invention:

[0034] The invention uses diphenyldichlorosilane, diethylene glycol and cyanuric chloride to prepare a chlorinated silicon-containing intermediate containing silicon and nitrogen elements. At the same time, the invention uses 5-chloromethylthiazole and an antioxidant p-phenylenediamine to undergo a substitution reaction to prepare a terminal amino group component one. Then, the component one and 3-aminopropyltrimethoxysilane are respectively subjected to a substitution reaction with the chlorinated silicon-containing intermediate to prepare a modified additive. Then, the silicon hydroxyl group in the structure of the modified additive is subjected to a condensation reaction with the hydroxyl group on the surface of nano-calcium carbonate, so that a thiazole structure with antibacterial activity and multiple anti-aging functional groups -NH are grafted on the surface of the nano-calcium carbonate, thereby giving the membrane material good antibacterial and aging resistance. At the same time, the introduced silicon element and nitrogen element can achieve synergistic flame retardancy. The invention has the effect of giving the film material good flame retardant properties. In addition, under the action of chemical bonds, the antioxidant p-phenylenediamine and the nano-calcium carbonate are tightly combined, which limits the migration of the antioxidant in the thermoplastic elastomer substrate. After the nano-calcium carbonate is modified by the modifying additive, the lipophilicity of the surface is improved, which is conducive to the dispersion of the nano-calcium carbonate in the film material substrate and avoids the performance defects caused by the agglomeration of the nano-calcium carbonate to a certain extent. Then, the present invention utilizes the copper ions in copper acetate to coordinate with the nitrogen atoms of the thiazole structure introduced into the functionalized nano-calcium carbonate structure to prepare the modified nano-calcium carbonate, wherein the copper ions can further improve the flame retardant and smoke suppression efficiency and antibacterial properties of the film material.

[0035] The invention performs epoxidation treatment on SBS to prepare ESBS, and uses 3-aminopropyltriethoxysilane to perform amino modification on nano titanium dioxide, and then covalently grafts the amino nano titanium dioxide and ESBS to prepare modified SBS with an organic-inorganic hybrid crosslinking structure. The modified SBS has better thermal stability and improves the compatibility of the nano titanium dioxide and SBS. The amino nano titanium dioxide is uniformly dispersed on the surface of ESBS to avoid agglomeration. The nano titanium dioxide, as an inorganic ultraviolet shielding agent, has good weather resistance and heat resistance, and has strong antibacterial and bactericidal ability after absorbing ultraviolet light energy due to its special photocatalytic activity, and can cooperate with modified nano calcium carbonate to give the membrane material excellent antibacterial performance and mechanical properties. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The SBS (linear, 30 / 70 block ratio) in the examples and comparative examples of the present invention was produced by Baling Petrochemical Co., Ltd.

[0038] Embodiment 1 A method for preparing modified nano calcium carbonate comprises the following steps:

[0039] (1) 2.5 g of diphenyldichlorosilane and 2.7 g of diethylene glycol were placed in a reactor, 100 mL of tetrahydrofuran solvent was added, and the mixture was stirred for 6 h. During the reaction, 2.1 g of triethylamine was added in batches to remove the hydrogen chloride produced by the reaction. After the reaction was completed, the mixture was filtered, rotary evaporated, and dried to obtain a silicon-containing intermediate;

[0040] (2) 16.9 g of the silicon-containing intermediate (Mr=392.4) and 3.5 g of sodium hydroxide were placed in a reactor, 100 mL of tetrahydrofuran solvent was added, the temperature was raised to 95° C., and the mixture was refluxed for 1.5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a mixed solution. 16.6 g of cyanuric chloride and 130 mL of acetone were placed in a reactor, the mixed solution was slowly added dropwise, and the reaction was continued for 5 h. After the reaction was completed, the mixture was filtered and dried to obtain a chlorinated silicon-containing intermediate;

[0041] (3) 2.6 g of 5-chloromethylthiazole and 2 g of triethylamine were placed in a reactor, 70 mL of acetonitrile solvent was added, the temperature was raised to 50° C., 2.2 g of p-phenylenediamine was added, and the reaction was stirred for 4 h. After the reaction was completed, the mixture was subjected to rotary evaporation, filtration, and drying to prepare component 1;

[0042] (4) 13.7 g of chlorosilane (Mr=688.2) and 8.1 g of triethylamine were placed in a reactor, 350 mL of acetonitrile solvent was added, the temperature was raised to 55° C., 8.3 g of component 1 (Mr=205.2) was added, and the mixture was stirred for 6 h. Then, a mixed solution of 7.2 g of 3-aminopropyltrimethoxysilane and 25 ml of acetonitrile was added, and the mixture was stirred for 4 h. After the reaction was completed, the mixture was subjected to rotary evaporation, washing, and drying to prepare a modified additive.

[0043] (5) 5 g of nano-calcium carbonate was ultrasonically dispersed in 100 mL of toluene to obtain a suspension, 6.7 g of the modified additive was dissolved in 50 mL of toluene to obtain a mixed solution, the mixed solution was added to the suspension, and the mixture was stirred at 90° C. for 6 h. After the reaction was completed, the functionalized nano-calcium carbonate was prepared by filtration, washing, and drying;

[0044] (6) 5 g of functionalized nano-calcium carbonate was ultrasonically dispersed in 120 mL of anhydrous ethanol to obtain a dispersion, and then a mixed solution of 0.8 g of copper acetate and 100 mL of anhydrous ethanol was added, and the mixture was stirred at 75° C. for 3 h. After the reaction was completed, the modified nano-calcium carbonate was prepared by filtration, washing, and drying.

[0045] Embodiment 2 A method for preparing a modified SBS comprises the following steps:

[0046] A. Take 11g of SBS in a reactor, add 100mL of cyclohexane solvent, heat and stir until SBS is dissolved, then add 1.1g of formic acid, 0.11g of PEG-400 and 4.9mL of hydrogen peroxide, stir and react at 70°C for 2.5h, cool to room temperature after the reaction is completed, precipitate with anhydrous ethanol, wash and dry to prepare ESBS;

[0047] B. Take 5 g of nano titanium dioxide and ultrasonically disperse it in 200 mL of anhydrous ethanol, then add 14.2 g of 3-aminopropyltriethoxysilane, stir and react at 85 ° C for 8 hours, cool to room temperature after the reaction is completed, filter, wash and dry to prepare amino nano titanium dioxide;

[0048] C. Take 3g ESBS in a reactor, add 50mL cyclohexane solvent, heat to 70°C, stir to dissolve, add 2mL 0.25mol / L sodium hydroxide solution and 0.7g amino nano-titanium dioxide, stir to react for 3h, cool to room temperature after the reaction is completed, precipitate with anhydrous ethanol, wash and dry to prepare modified SBS.

[0049] Example 3 A TPE protective film for a liquid crystal display light guide plate comprises the following components in parts by weight: 62 parts of modified SBS prepared in Example 2, 12 parts of polypropylene, 5 parts of modified nano-calcium carbonate prepared in Example 1, 1.2 parts of lubricant stearic acid, and 0.7 parts of plasticizer dibutyl phthalate.

[0050] The method for preparing the TPE protective film for the liquid crystal display light guide plate comprises the following steps:

[0051] S1, adding parts by weight of modified SBS, polypropylene, modified nano calcium carbonate, lubricant and plasticizer into a mixer, mixing at 50° C. for 10 min to obtain a premix;

[0052] S2, extruding and granulating the premixed material at 185° C. in a twin-screw extruder to obtain a mixed material;

[0053] S3, blow molding the mixed material to prepare a TPE protective film for a liquid crystal display light guide plate.

[0054] Example 4 A TPE protective film for a liquid crystal display light guide plate comprises the following components in parts by weight: 70 parts of modified SBS prepared in Example 2, 15 parts of polypropylene, 7 parts of modified nano-calcium carbonate prepared in Example 1, 2 parts of lubricant polyethylene wax, and 1.2 parts of plasticizer diisononyl phthalate.

[0055] The preparation method of the above-mentioned TPE protective film for the liquid crystal display light guide plate is the same as that of Example 3.

[0056] Example 5 A TPE protective film for a liquid crystal display light guide plate comprises the following components in parts by weight: 78 parts of modified SBS prepared in Example 2, 20 parts of polypropylene, 9 parts of modified nano calcium carbonate prepared in Example 1, 2.5 parts of lubricant oxidized polyethylene wax, and 1.4 parts of plasticizer tributyl citrate.

[0057] The preparation method of the above-mentioned TPE protective film for the liquid crystal display light guide plate is the same as that of Example 3.

[0058] Comparative Example 1 A method for preparing modified nano calcium carbonate comprises the following steps:

[0059] (1) 2.5 g of diphenyldichlorosilane and 2.7 g of diethylene glycol were placed in a reactor, 100 mL of tetrahydrofuran solvent was added, and the mixture was stirred for 6 h. During the reaction, 2.1 g of triethylamine was added in batches to remove the hydrogen chloride produced by the reaction. After the reaction was completed, the mixture was filtered, rotary evaporated, and dried to obtain a silicon-containing intermediate;

[0060] (2) 16.9 g of the silicon-containing intermediate (Mr=392.4) and 3.5 g of sodium hydroxide were placed in a reactor, 100 mL of tetrahydrofuran solvent was added, the temperature was raised to 95° C., and the mixture was refluxed for 1.5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a mixed solution. 16.6 g of cyanuric chloride and 130 mL of acetone were placed in a reactor, the mixed solution was slowly added dropwise, and the reaction was continued for 5 h. After the reaction was completed, the mixture was filtered and dried to obtain a chlorinated silicon-containing intermediate;

[0061] (3) 13.7 g of chlorosilane (Mr=688.2) and 4 g of triethylamine were placed in a reactor, 350 mL of acetonitrile solvent was added, the temperature was raised to 55° C., a mixed solution of 7.2 g of 3-aminopropyltrimethoxysilane and 25 ml of acetonitrile was added, and the reaction was continued with stirring for 4 h. After the reaction was completed, the modified additive was prepared by rotary evaporation, washing, and drying;

[0062] (4) 5 g of nano-calcium carbonate was ultrasonically dispersed in 100 mL of toluene to obtain a suspension, 5 g of the modified additive was dissolved in 50 mL of toluene to obtain a mixed solution, the mixed solution was added to the suspension, and the mixture was stirred at 90° C. for 6 h. After the reaction was completed, the functionalized nano-calcium carbonate was prepared by filtration, washing, and drying;

[0063] (5) 5 g of functionalized nano-calcium carbonate was ultrasonically dispersed in 120 mL of anhydrous ethanol to obtain a dispersion, and then a mixed solution of 0.8 g of copper acetate and 100 mL of anhydrous ethanol was added, and the mixture was stirred at 75° C. for 3 h. After the reaction was completed, the modified nano-calcium carbonate was prepared by filtration, washing, and drying.

[0064] Comparative Example 2 A method for preparing modified nano calcium carbonate comprises the following steps:

[0065] (1) 2.5 g of diphenyldichlorosilane and 2.7 g of diethylene glycol were placed in a reactor, 100 mL of tetrahydrofuran solvent was added, and the mixture was stirred for 6 h. During the reaction, 2.1 g of triethylamine was added in batches to remove the hydrogen chloride produced by the reaction. After the reaction was completed, the mixture was filtered, rotary evaporated, and dried to obtain a silicon-containing intermediate;

[0066] (2) 16.9 g of the silicon-containing intermediate (Mr=392.4) and 3.5 g of sodium hydroxide were placed in a reactor, 100 mL of tetrahydrofuran solvent was added, the temperature was raised to 95° C., and the mixture was refluxed for 1.5 h. After the reaction was completed, the mixture was cooled to room temperature to obtain a mixed solution. 16.6 g of cyanuric chloride and 130 mL of acetone were placed in a reactor, the mixed solution was slowly added dropwise, and the reaction was continued for 5 h. After the reaction was completed, the mixture was filtered and dried to obtain a chlorinated silicon-containing intermediate;

[0067] (3) 2.6 g of 5-chloromethylthiazole and 2 g of triethylamine were placed in a reactor, 70 mL of acetonitrile solvent was added, the temperature was raised to 50° C., 2.2 g of p-phenylenediamine was added, and the reaction was stirred for 4 h. After the reaction was completed, the mixture was subjected to rotary evaporation, filtration, and drying to prepare component 1;

[0068] (4) 13.7 g of chlorosilane (Mr=688.2) and 8.1 g of triethylamine were placed in a reactor, 350 mL of acetonitrile solvent was added, the temperature was raised to 55° C., 8.3 g of component 1 (Mr=205.2) was added, and the mixture was stirred for 6 h. Then, a mixed solution of 7.2 g of 3-aminopropyltrimethoxysilane and 25 ml of acetonitrile was added, and the mixture was stirred for 4 h. After the reaction was completed, the mixture was subjected to rotary evaporation, washing, and drying to prepare a modified additive.

[0069] (5) 5 g of nano-calcium carbonate was ultrasonically dispersed in 100 mL of toluene to obtain a suspension, 6.7 g of the modified additive was dissolved in 50 mL of toluene to obtain a mixed solution, the mixed solution was added to the suspension, and the mixture was stirred at 90° C. for 6 h. After the reaction was completed, the modified nano-calcium carbonate was prepared by filtration, washing, and drying.

[0070] Comparative Example 3 A TPE protective film for a liquid crystal display light guide plate comprises the following components in parts by weight: 78 parts of modified SBS prepared in Example 2, 20 parts of polypropylene, 9 parts of modified nano-calcium carbonate prepared in Comparative Example 1, 2.5 parts of lubricant oxidized polyethylene wax, and 1.4 parts of plasticizer tributyl citrate.

[0071] The preparation method of the above-mentioned TPE protective film for the liquid crystal display light guide plate is the same as that of Example 3.

[0072] Comparative Example 4 A TPE protective film for a liquid crystal display light guide plate comprises the following components in parts by weight: 78 parts of modified SBS prepared in Example 2, 20 parts of polypropylene, 9 parts of modified nano-calcium carbonate prepared in Comparative Example 2, 2.5 parts of lubricant oxidized polyethylene wax, and 1.4 parts of plasticizer tributyl citrate.

[0073] The preparation method of the above-mentioned TPE protective film for the liquid crystal display light guide plate is the same as that of Example 3.

[0074] Comparative Example 5 A TPE protective film for a liquid crystal display light guide plate comprises the following components in parts by weight: 78 parts of modified SBS prepared in Example 2, 20 parts of polypropylene, 9 parts of nano calcium carbonate, 2.5 parts of lubricant oxidized polyethylene wax, and 1.4 parts of plasticizer tributyl citrate.

[0075] The preparation method of the above-mentioned TPE protective film for the liquid crystal display light guide plate is the same as that of Example 3.

[0076] Comparative Example 6 A TPE protective film for a liquid crystal display light guide plate comprises the following components in parts by weight: 63 parts of SBS, 15 parts of nano titanium dioxide, 20 parts of polypropylene, 9 parts of modified nano calcium carbonate prepared in Example 1, 2.5 parts of lubricant oxidized polyethylene wax, and 1.4 parts of plasticizer tributyl citrate.

[0077] The preparation method of the above-mentioned TPE protective film for the liquid crystal display light guide plate is the same as that of Example 3.

[0078] Performance testing:

[0079] The membrane materials prepared in Examples 3-5 and Comparative Examples 3-6 were tested for performance: the tensile performance of the samples was tested according to GB / T528-2008; the change rate of tensile strength was tested after aging at 100°C for 24h and 48h to evaluate the thermal oxygen aging resistance of the samples; the flame retardant performance of the samples was tested by limiting oxygen index; the antibacterial effect of the samples on Escherichia coli and Staphylococcus aureus was tested by plate count method, and the activated bacterial solution was added to the test tube and diluted to a total bacterial colony count of 10 6 CFU / mL, the membrane material was added to the bacterial solution, placed in a constant temperature incubator, and cultured at 37°C for 24 hours with shaking, then the diluted bacterial solution was coated on the agar medium, placed in a constant temperature incubator, and cultured at 37°C for 24 hours. The number of colonies in each culture dish was observed, and the number of colonies was used to calculate the inhibition rate = (R0-R1) / R0, where R0 is the number of colonies without adding membrane material, and R1 is the number of colonies with adding membrane material. The data results are shown in Table 1.

[0080] Table 1 Test results of sample performance

[0081]

[0082] It can be seen from the data in Table 1 that the membrane materials prepared in Examples 3-5 of the present invention have high tensile strength, and still have high tensile strength after aging at 100° C. for 24 h and 48 h, and have excellent aging resistance, as well as excellent antibacterial and flame retardant effects. Among them, the modified nano-calcium carbonate component in Comparative Example 3 is not grafted with component one, and its measured antibacterial effect and aging resistance are lower than those of Examples 3-5. The reason is that the thiazole structure and the antioxidant p-phenylenediamine are not introduced into the modified nano-calcium carbonate structure. In Comparative Example 4, copper ions are not introduced into the modified nano-calcium carbonate component, and its measured antibacterial rate and limiting oxygen index are lower than those of Examples 3-5, indicating that the coordination of copper ions can improve the antibacterial effect and flame retardant properties of the membrane material to a certain extent. In Comparative Example 5, the nano-calcium carbonate is not modified, and its measured tensile strength, tensile strength change rate, antibacterial rate and limiting oxygen index are most significantly lower than those of Examples 3-5. In Comparative Example 6, SBS and nano-titanium dioxide are not grafted, and its measured tensile strength is significantly lower than that of Examples 3-5. The possible reason is that the agglomeration of nano-titanium dioxide leads to a decrease in its tensile strength.

[0083] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0084] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A TPE protective film for a liquid crystal display light guide plate, characterized in that: The invention comprises the following components by weight: 60-80 parts of modified SBS, 10-20 parts of polypropylene, 5-10 parts of modified nano calcium carbonate, 1-3 parts of lubricant, and 0.5-1.5 parts of plasticizer; The modified nano-calcium carbonate is prepared by grafting a modified additive on the surface of the nano-calcium carbonate by chemical reaction and then coordinating with copper ions; wherein the modified additive is prepared by using diphenyldichlorosilane, diethylene glycol, and cyanuric chloride as raw materials to prepare a chlorinated silicon-containing intermediate, and then grafting component one and 3-aminopropyltrimethoxysilane; wherein component one is prepared by a substitution reaction between 5-chloromethylthiazole and p-phenylenediamine; The structural formula of the chlorinated silicon-containing intermediate is as follows: The modified SBS is prepared by a ring-opening reaction between epoxidized SBS and nano-titanium dioxide modified by amination with 3-aminopropyltriethoxysilane.

2. The TPE protective film for liquid crystal display light guide plate according to claim 1, characterized in that: The lubricant is one or more of stearic acid, polyethylene wax, oxidized polyethylene wax, and paraffin wax; the plasticizer is one or more of dibutyl phthalate, diisononyl phthalate, tributyl citrate, and acetyl tributyl citrate.

3. The TPE protective film for liquid crystal display light guide plate according to claim 1, characterized in that: The preparation method of the modified nano calcium carbonate comprises the following steps: (1) diphenyldichlorosilane and diethylene glycol are placed in a reactor, tetrahydrofuran solvent is added, and the reaction is stirred for 5 to 7 hours. During the reaction, triethylamine is added in batches to remove hydrogen chloride generated by the reaction. After the reaction is completed, the reaction is filtered, rotary evaporated, and dried to prepare a silicon-containing intermediate; (2) Put the silicon-containing intermediate and sodium hydroxide in a reactor, add tetrahydrofuran solvent, heat to 80-95° C., reflux for 1-2 hours, cool to room temperature after the reaction is completed to obtain a mixed solution, put cyanuric chloride and acetone in a reactor, slowly dropwise add the mixed solution and continue to react for 3-5 hours, filter and dry after the reaction is completed to prepare a chlorinated silicon-containing intermediate; (3) 5-chloromethylthiazole and triethylamine are placed in a reactor, acetonitrile solvent is added, the temperature is raised to 45-55° C., p-phenylenediamine is added, and stirred for 2-5 hours. After the reaction is completed, the mixture is subjected to rotary evaporation, filtration, and drying to prepare component 1; (4) taking the chlorinated silicon-containing intermediate and triethylamine into a reactor, adding acetonitrile solvent, heating to 40-60° C., adding component 1 and stirring the reaction for 4-7 hours, then adding a mixed solution of 3-aminopropyltrimethoxysilane and acetonitrile, continuing to stir the reaction for 4-6 hours, and after the reaction is completed, rotary evaporation, washing, and drying are performed to prepare a modified additive; (5) dispersing nano-calcium carbonate in toluene by ultrasonic method to obtain a suspension, dissolving the modified additive in toluene to obtain a mixed solution, adding the mixed solution to the suspension, stirring and reacting at 85-95° C. for 5-7 hours, and filtering, washing and drying after the reaction is completed to obtain functionalized nano-calcium carbonate; (6) The functionalized nano-calcium carbonate is ultrasonically dispersed in anhydrous ethanol to obtain a dispersion, and then a mixed solution of copper acetate and anhydrous ethanol is added, and the mixture is stirred and reacted at 60-75° C. for 2-3 hours. After the reaction is completed, the modified nano-calcium carbonate is prepared by filtration, washing, and drying.

4. The TPE protective film for a liquid crystal display light guide plate according to claim 3, characterized in that: In the step (1), the molar ratio of diphenyldichlorosilane to diethylene glycol is 1:2.2-2.

7.

5. The TPE protective film for liquid crystal display light guide plate according to claim 3, characterized in that: In the step (2), the molar ratio of the silicon-containing intermediate, sodium hydroxide and cyanuric chloride is 1:2-2.1:2-2.

2.

6. The TPE protective film for a liquid crystal display light guide plate according to claim 3, characterized in that: In the step (3), the molar ratio of 5-chloromethylthiazole to p-phenylenediamine is 1:1 to 1.

3.

7. The TPE protective film for a liquid crystal display light guide plate according to claim 3, characterized in that: In the step (4), the molar ratio of the chlorinated silicon-containing intermediate, component one and 3-aminopropyltrimethoxysilane is 1:2-2.2; 2-2.

2.

8. The TPE protective film for a liquid crystal display light guide plate according to claim 3, characterized in that: In the step (5), the mass ratio of nano calcium carbonate to the modified additive is 1:0.5-2.

9. The TPE protective film for a liquid crystal display light guide plate according to claim 1, characterized in that: The preparation method of the modified SBS comprises the following steps: A. Take SBS in a reactor, add cyclohexane solvent, heat and stir until SBS is dissolved, then add formic acid, PEG-400 and hydrogen peroxide, stir and react at 65-80°C for 2-3h, cool to room temperature after the reaction is completed, precipitate with anhydrous ethanol, wash and dry to prepare ESBS; B. Ultrasonic dispersion of nano-titanium dioxide in anhydrous ethanol, then adding 3-aminopropyltriethoxysilane, stirring and reacting at 75-90° C. for 6-8 hours, cooling to room temperature after the reaction is completed, filtering, washing and drying to prepare amino-modified nano-titanium dioxide; C. Take ESBS in a reactor, add cyclohexane solvent, heat to 65-75°C, stir to dissolve, add sodium hydroxide solution and amino-modified nano-titanium dioxide, stir to react for 2.5-4h, cool to room temperature after the reaction is completed, precipitate with anhydrous ethanol, wash and dry to prepare modified SBS.

10. A method for preparing a TPE protective film for a liquid crystal display light guide plate according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, adding parts by weight of modified SBS, polypropylene, modified nano calcium carbonate, lubricant and plasticizer into a mixer, mixing at 40-60° C. for 5-10 min to obtain a premix; S2, extruding and granulating the premixed material at 170-200° C. in a twin-screw extruder to obtain a mixed material; S3, blow molding the mixed material to prepare a TPE protective film for a liquid crystal display light guide plate.

Citation Information

Patent Citations

  • A homogeneous and stable wear-resistant TPE material and its preparation method

    CN115246978B

Cited By

  • Impact-resistant polypropylene composite material as well as production method and application thereof

    CN120248498A